Employment of University Graduates in Modern China: Expectations and Reality - V. V. Kuznetsova; O. A. Mashkina (Сравнительная политика)
The employment of China's tertiary education system’s graduates is considered, on the one hand, as a prerequisite for the implementation of the strategic goal set by the Chinese leadership – turning the country into a global center for the development of new knowledge and technologies by 2035, and on the other, as a factor of ensuring social stability. The analysis shows that an increasingly serious problem is the contradiction between the prevailing ideas in Chinese society about importance of “high scholarship” and the structure of vacancies for graduates of universities and higher professional colleges in the labor market; between the ideas of graduates about what kind of knowledge and skills are in demand by employers, and the requirements imposed by employers on applicants while searching for qualiﬁed personnel.